How to speak cat! - Whitehead, Sarah (Gosford, N.S.W. : Scholastic, 2008)
If your cat could talk, what would she say? How to Speak Cat! can help you discover why she waves her tail, how she tells you when she wants to play, and why she purrs. Find out how you can talk to your pet so she'll respond in just the way you want, from training her to use the kitty litter, to letting her know it's time for dinner. All cats talk. You just have to know the language!
7 yrs+
Cats.
Includes index.
Keywords: Cats -- Behavior; Animal communication; Human-animal communication